Research IMPLEMENTASI METODE DISKUSI DALAM PEMAHAMAN TEKS ARAB SISWA MADRASAH I’DADIYAH - Almannah Wassalwa Wassalwa (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2023)
Discussion methods is the intraction to exchange ideas, and information for problem solving and the implementation discussion methods is teacher give the opportunity to extend their opinion and the teacher assembled the conclusion of their opinion it’s be alternative for problem solving discussion to search an agreement. Methods : this study used a qualitative methods the result of the study is descriptive and data collection techniques is interview, Observation, and Documentation. According to the result of the study and analyze of data that used by researcher in the second wustho class of Islamic school I’dadiyah PP. Salafiyah Syafi’iyah Sukorejo Situbondo, The result of study is : The implementation of discussion methods maked do by the teacher to divide into separate parts of group discussion and the teacher give a text or a problem to discuss in every group, in this moment the teacher also give a guidelines or direction. In other that students have opportunity to explain of their opinion, and for the last stage, the teacher assembled the conclusion and evaluation of discuss activity. The student ability for comprehension or understanding Arabic text with used discussion method is good enough cause it be evaluated by standard completeness value. Keywords : Discussin Methods, Comprehension Arabic Text.